(untitled) (Global Journal of Medical Research, 2018)
Distal biceps tendon rupture is a fairly uncommon injury but the incidence has risen with the associated increase in recreational activities in the 40 to 60 year old age group. The injury usually occurs from a single traumatic event whereby there is a forceful eccentric contraction of the biceps in the flexed elbow. Management considerations include conservative versus surgical management, and if surgery is chosen, the surgical approach: one-incision versus two-incision, and the choice of fixation technique which includes: suture anchors, bone tunnels or the endobutton. Surgery is indicated in patients who require maximum flexion and supination strength for vocational and recreational activities. The following article discusses the evolution of surgical management and the complications associated with the one and two incision approaches.